Kinetic modelling of yeast growth and pollutant removal in secondary effluent. (December 2022) - Mohiuddin, Obaidullah; Harvey, Adam P; Tabraiz, Shamas; Ameen, Muhammad Tahir; Velasquez-Orta, Sharon
Abstract: In recent years, there has been significant interest in yeast-based wastewater treatment due to its high pollutant removal rate and ability to perform in non-sterile environments. In this work, a kinetic model was developed to predict yeast growth and substrate consumption during wastewater treatment. To determine the biological constants for use in the kinetic models, a unique approach is presented. Candida utilis was cultivated in synthetic wastewater, using eight different ratios of carbon, nitrogen and phosphorus to determine its growth rate, and the removal rates of carbon, nitrogen, and phosphorus. The concentrations of C, N and P were chosen within the range of secondary effluent wastewater. In all experiments, carbon was found to be the limiting substrate, and 100 % TOC removal was achieved in all cases. Candida utilis reduced the COD concentration by up to 99 % in <24 h. In the model, both yeast growth and substrate consumption were satisfactorily described by Monod kinetics. The apparent half-saturation coefficients for carbon, nitrogen, and phosphorus, determined via the optimization of the model, were found to the function of initial substrate concentration. The maximum specific growth rate found was 0.59 h −1 . This model was used on different initial concentrations of substrates, and predicted data with an R 2 above 80 %. Both model and experimental results suggest that Candida utilis can be used in the tertiary treatment of wastewater. The simple approach described here can be applied to find biological coefficients for other microorganisms. Highlights: A mathematical approach is presented to determine the biological constant for multi-substrate Monod kinetics. Half-saturation is not constant but is dependent upon the initial concentration of substrates. Change in pH does not affect the relation of the half-saturation coefficient to initial substrate concentration. Only the substrate removal coefficient/Yield coefficient varies with respect to pH.